Theoretıcal Analysıs of the Movement of Raw Cotton ın Unıform Feeder Feed ın the New Installatıon - Kaybnazarov E. E., Sultanov O. S., Muhsinov I.I., Sultanov S. Y. (International Journal of Advanced Science and Technology, 2020)
Integrated circuits are in demand to be invetigated for its economical performance. Therefore, it is vialbe to experiment on ternary based operations[7]. A ternary half adder based on ternary multiplexer and logic primitives is proposed and its performance is analyzed in detail. This proposed ternary half is sensibly designed with the simplified expressions using the ternary k-map. The combinational logic blocks for the SUM and CARRY are designed, verified, constructed and simulated with Tanner EDA (130nm) at 1.2 V.